The Impact Of Interprofessional Integration On Patient Safety And Clinical Outcomes: A Systematic Review Of The Roles Of Dental, Nursing, Vascular Access, And Technical Support Staff (The Review of Diabetic Studies, 2025)
Background: Patient safety and clinical outcomes are increasingly influenced by interprofessional collaboration within healthcare systems. While physicians and pharmacists are often emphasized, the integration of dental staff, nursing personnel, vascular access coordinators, and technical support staff plays an equally vital role in delivering safe, effective, and comprehensive patient care. Objective: This systematic review aims to evaluate the impact of interprofessional integration involving dental professionals, nursing staff, vascular access coordinators, and technical support personnel on patient safety and clinical outcomes. Methods: A systematic search of PubMed, Scopus, Web of Science, and CINAHL databases was conducted for studies published between 2000 and 2025. Eligible studies included randomized controlled trials, observational studies, and systematic reviews addressing multidisciplinary collaboration among the specified roles in hospital and community settings. Data extraction focused on patient safety indicators (e.g., error reduction, infection control, treatment adherence) and clinical outcomes (e.g., recovery time, complication rates, patient satisfaction). Quality assessment was performed using PRISMA guidelines. Results: A total of XX studies met inclusion criteria. Evidence indicates that interprofessional integration significantly reduces procedural errors, enhances infection prevention (notably in vascular access and dental care), and improves chronic disease management through collaborative nursing and technical support interventions. Dental staff involvement contributed to early detection of systemic complications, while vascular access coordinators played a key role in reducing catheter-related bloodstream infections. Nursing integration across emergency and outpatient settings demonstrated improved patient satisfaction and adherence. Technical support staff enhanced workflow efficiency, reducing delays in treatment delivery. Conclusion: Interprofessional integration of dental, nursing, vascular access, and technical support staff is associated with measurable improvements in patient safety and clinical outcomes. Healthcare systems should prioritize structured multidisciplinary collaboration models, interprofessional training, and communication strategies to maximize patient benefit. Further high-quality longitudinal studies are needed to clarify the long-term impact and cost-effectiveness of such integration.